The IMF's Reserves Template and Nominal Exchange Rate Volatility - Gonzalez-Garcia, Jesus (IMF Working Papers; Working Paper, 2006)
The effects of the adoption of the IMF's International Reserves and Foreign Currency Liquidity Data Template on nominal exchange rate volatility are investigated for 48 countries. Estimation of panel data models indicates that nominal exchange rate volatility decreases following dissemination of reserves template data while the effects of indebtedness and reserve adequacy on volatility exhibit statistically significant changes.